A Polymorphism at the Translation Start Site of the Vitamin D Receptor Gene Is Associated with the Response to Anti-Osteoporotic Therapy in Postmenopausal Women from Southern Italy - Valeria Conti (International Journal of Molecular Sciences, 2015)
The present study investigated the effect of two single nucleotide polymorphisms (SNPs) of the vitamin D receptor (VDR) gene, rs1544410 A/G and rs2228570 C/T, in modulating bone mineral density (BMD) and the response to treatment with bisphosphonates or strontium ranelate in postmenopausal osteoporosis (PMO). Four hundred eighteen postmenopausal women from Southern Italy treated with bisphosphonates or strontium ranelate for three years were enrolled and stratified according to their genotype. Changes in BMD were expressed as the delta t-score (Δt-score). Allelic frequencies for rs1544410 A/GSNP were 11.2% AA, 50.0% GA and 38.8% GG; for rs2228570 C/TSNP were 54.8% CC, 39.5% TC and 5.7% TT. TT carriers showed a lower t-score than TC and CC (both p < 0.02) genotypes and were more responsive to the therapy when compared to both TC (p < 0.02) and CC (p < 0.05) carriers. Specifically, TT carriers receiving alendronate demonstrated a significant improvement of the Δt-score compared to TC and CC (both p < 0.0001) carriers. After adjustment for confounders, the Δt-score showed evidence of a statistically significant positive association with TT in all treatments considered. Therapy response was independent of rs1544410 A/G SNP; instead, rs2228570 C/TSNP was associated with a better response to antiresorptive treatment, thus suggesting that the therapy for PMO should be personalized.